2017
DOI: 10.1111/epi.13851
|View full text |Cite
|
Sign up to set email alerts
|

Voxel‐based magnetic resonance image postprocessing in epilepsy

Abstract: SummaryObjectiveAlthough the general utility of voxel‐based processing of structural magnetic resonance imaging (MRI) data for detecting occult lesions in focal epilepsy is established, many differences exist among studies, and it is unclear which processing method is preferable. The aim of this study was to compare the ability of commonly used methods to detect epileptogenic lesions in magnetic resonance MRI‐positive and MRI‐negative patients, and to estimate their diagnostic yield.MethodsWe identified 144 pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
40
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 43 publications
(49 citation statements)
references
References 30 publications
7
40
0
2
Order By: Relevance
“…It can be expected that visual interpretation improves the specificity by eliminating false positive findings through expert knowledge. As predicted, specificity across models was higher after visual inspection, but also resulting in a decreased concordant rate, which is in line with previous studies (Kotikalapudi et al, ; Martin et al, ; Wang et al, ). The automated VBM process also had a relevant high number of discordant findings, which reduced after the visual analysis.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…It can be expected that visual interpretation improves the specificity by eliminating false positive findings through expert knowledge. As predicted, specificity across models was higher after visual inspection, but also resulting in a decreased concordant rate, which is in line with previous studies (Kotikalapudi et al, ; Martin et al, ; Wang et al, ). The automated VBM process also had a relevant high number of discordant findings, which reduced after the visual analysis.…”
Section: Discussionsupporting
confidence: 92%
“…As predicted, specificity across models was higher after visual inspection, but also resulting in a decreased concordant rate, which is in line with previous studies Martin et al, 2017;Wang et al, 2015). The automated VBM process also had a relevant high number of discordant findings, which reduced after the visual analysis.…”
Section: Visual Interpretation Of Vbm Findingssupporting
confidence: 90%
See 2 more Smart Citations
“…Also, past studies used variable smoothing (between 5 and 14 mm) [7][8][9] and statistical cutoffs to elucidate VBM findings. 10,11 Studies have shown that changing smoothing kernel size 9 and statistical thresholds have a direct impact on the VBM findings, 10 also affecting the specificity of the results. 10 Recently, multispectral VBM (ie, the combination of multiple MR imaging contrast sequences) was proposed and made available in SPM8/SPM12 (http://www.fil.ion.ucl.ac.uk/spm/software/ spm12) within its unified segmentation framework (New Segment).…”
mentioning
confidence: 99%